Framing improvements of public innovation in a living lab context: Processual learning, restrained space and democratic engagement - Fuglsang, Lars; Hansen, Anne Vorre (Research Policy, 2022)
Public innovation has received increasing attention in recent years. Experiments with new governance structures, such as New Public Management and New Public Governance, have challenged the traditional top-down, internally driven forms of innovation in the public sector and have entailed a search for new forms of open, collaborative and interactive innovation, implying a reframing of public innovation activities. However, introducing these new frames of innovation causes uncertainties in the public sector, necessitating better understanding of how public innovation can be changed to address societal needs. This paper uses materials from case studies of 21 public living labs across Europe to analyse the lessons that can be learned from public sector participation in living labs in terms of their contribution to reframing public innovation. The “frame” construct is used to analyse and provide an understanding of how participation in living labs helps public actors to reframe innovation and address public and societal needs. Three living lab framings for changing public innovation are identified (processual learning, restrained space and democratic engagement), and the degree of intensity of these framings with respect to involving stakeholders and addressing societal challenges is discussed. The paper contributes to knowledge of public sector innovation by extending previous accounts of how public innovation can be improved.
Number: 1
Keywords: Europe; Innovation publique; Laboratoire vivant; Libre accès; Living Labs

Laboratoires vivants en innovation sociale et coconstruction des connaissances dans les villes : les cas du TIESS (Montréal) et de l’OBISF (Florianópolis) - Magalhaes, Thiago; Camus, Annie; Andion, Carolina; Tello-Rozas, Sonia (Revue Organisations & territoires, 2020)
Le débat sur le rapport entre l’innovation sociale et les villes s’est élargi au cours des dernières décennies. Ce débat met en évidence l’intérêt suscité par les processus de coconstruction des savoirs dans les laboratoires vivants en innovation sociale (LVIS). Cet article a pour objectif de présenter une approche conceptuelle et analytique du traitement des LVIS, ainsi que de décrire et de mettre en perspective deux expériences de mise en oeuvre de LVIS dans les villes : l’Observatoire de l’innovation sociale de Florianópolis (OBISF) au Brésil et Territoires innovants en économie sociale et solidaire (TIESS) à Montréal au Canada. Bien qu’ils émergent dans des réalités et des contextes différents avec des méthodologies de mise en oeuvre spécifiques, qui sont présentées dans le texte, la discussion et l’analyse des deux cas apportent des pistes d’apprentissage sur les défis et les perspectives quant à la coconstruction des connaissances visant à renforcer les dynamiques d’innovation sociale à l’échelle d’une ville.
Number: 2
Keywords: Brésil; Canada; Co-construction; Laboratoire vivant; Living Labs; Montréal; Réservé UdeM; Urbanisme; Économie sociale; Économie solidaire

Le living lab, un intermédiaire d’innovation ouverte pour les territoires ruraux ou péri-urbains ? - Fasshauer, Ingrid; Zadra-Veil, Cathy (Innovations, 2020)
L’objectif de cet article est d’analyser une nouvelle forme organisationnelle, le living lab (LL) et sa capacité à favoriser l’innovation territoriale en milieu rural ou péri-urbain. A travers une revue de littérature et la mobilisation de la sociologie de l’acteur-réseau (Callon, 1986 ; Latour, 1987), nous positionnons les living labs comme intermédiaires d’innovation ouverte dont les caractéristiques permettent d’intégrer de nombreux acteurs hétérogènes, établissements publics, entreprises privées, associations et citoyens, sur des projets d’innovation. L’étude d’un LL rural met en évidence la capacité d’une telle structure à reconfigurer des réseaux d’acteurs pour proposer une série de tiers-lieux adaptés aux spécificités des territoires sur lesquels ils s’implantent. Cette recherche permet d’enrichir la réflexion la pérennisation des tiers-lieux ruraux et leurs spécificités par rapport aux espaces urbains.
Number: 1 Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 1 Publisher: De Boeck Supérieur
Keywords: Collaboration; Innovation; Innovation ouverte; Laboratoire vivant; Living Labs; Réservé UdeM; Économie collaborative

Open social innovation dynamics and impact: exploratory study of a fab lab network - Rayna, Thierry; Striukova, Ludmila (R&D Management, 2019)
The aim of this research is to explore the dynamics and impact of open social innovation, within the context of fab labs and makerspaces. Using an exploratory methodology based on 12 semi-structured interviews of fab lab founders belonging to The Centres for Maker Innovation and Technology (CMIT) programme – a network of 170 fab labs located in Eastern Europe – this research explores the impact of an adopting an open approach in relation to the different stages of social innovation (prompts, proposals, prototypes, sustaining, scaling and diffusion, systemic change) as well as social impact. The main results of this study are that while the CMIT programme provided each fab lab with similar initial conditions (identical funding, objectives and rules), the open social innovation approached adopted enabled to give birth to a wide diversity of fab labs, each being very well adapted to the local environment, social needs and constraints and able to deliver social impact in just a matter of years; a result that would be hard to achieve with a centralised top-down approach. The study identified three types of CMITs – Education, Industry and Residential – which could be similar or different depending on the stage of social open innovation. Furthermore, this paper discusses the main difficulties social entrepreneurs encounter as a part of the open social innovation process, as well as means to overcome them. In this respect, this study adds to the literature on fab labs by providing more comprehensive view of the challenges faced by fab labs (and makerspaces) founders, as well as suggestions of strategies enabling to ensure their long-term sustainability.
Number: 3 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/radm.12376
Keywords: Innovation ouverte; Laboratoire vivant; Living Labs; Mesure d'impact; Réservé UdeM

University Medialabs: New Learning Spaces for Educational Innovation - Almaraz-Menéndez, Fernando; Martín-García, Teresa; López-Esteban, Carmen (Journal of Strategic Innovation and Sustainability, 2021)
Higher Education Institutions, like many other organizations, are facing pressure from the development of digital technologies as a push towards the digitization of their activities and towards a type of change that some describe as disruptive and that forces them to review their processes and structures. This article describes the case of the medialab of the University of Salamanca, MEDIALAB USAL, as an experience of new learning space in higher education. Its origin is explained from the experiences of citizen technology laboratories and experimental laboratories at the point of intersection between Art, Science and Technology. Its structure and working methods are explained, and its activities are illustrated through the description of four educational innovation projects based on different digital technologies: a mathematics didactics project using AppInventor, Wikipedia as a tool for knowledge generation, Arduino for innovation in the teaching of Fine Arts and a university Hackathon as an activity to introduce students to social and entrepreneurial innovation processes.
Number: 4
Keywords: Collaboration; Durabilité; Europe; Innovation pédagogique; Innovation sociale; Laboratoire vivant; Libre accès; Living Labs; Rôle des universités; Technologies; numérique

Webinar | Place-based Social Innovation Through Living Labs - Institute Tamarack (2021)
This webinar includes the experiences and insights from two Québec-based organizations with an approach that yields a huge potential for transformative change.
Directors: _:n274
Keywords: Innovation sociale; Laboratoire vivant; Libre accès; Living Labs; Québec; Webinaire

La transformation sociale par l'innovation sociale - Klein, Juan-Luis; Jetté, Christian; Champagne, Christine; Roy, Matthieu (Presses de l'Université du Québec, 2016)
Les innovations sociales, à la manière de bougies d’allumage, engendrent des actions collectives qui proposent des solutions différentes de celles des pratiques dominantes en mettant l’économie au service des personnes et de la société. Or la simple multiplication des innovations sociales ne peut générer la transformation sociale à elle seule. La mise en relation des mouvements sociaux et de leur visée émancipatoire est nécessaire pour façonner de nouvelles normes et règles et mettre en place de nouveaux sentiers institutionnels. Ce sont certains de ces nouveaux sentiers que montrent les textes regroupés dans cet ouvrage. Fruit du ive Colloque international du Centre de recherche sur les innovations sociales, il expose les enjeux que pose la trans-formation sociale par l’innovation sociale et les documente par des illustrations ciblées sur des thématiques ou des expériences précises. Une discussion théorique sur le lien entre l’innovation sociale et la transformation sociale est d’abord proposée, puis les méthodes d’analyse de l’innovation sociale, le partage de connaissance entre les chercheurs et les acteurs sociaux, le rôle de l’État et des politiques publiques, l’économie solidaire et la place de l’entreprise sociale sont abordés. L’ensemble des textes analytiques et des textes illustratifs de cet ouvrage offre des pistes de réflexion sur la transformation sociale par l’inno-vation sociale, c’est-à-dire sur la façon dont certaines expérimen-tations aboutissent à la transformation de la société. L’ouvrage met ainsi de l’avant le rôle des citoyens et des organisations qui travaillent pour le bien-être des collectivités en expérimentant des solutions à leurs problèmes et en se mobilisant pour exiger leur reconnaissance. Il vise à poser les jalons pour comprendre et participer à la reconstruction sociale déjà à l’œuvre, dans le but de la renforcer.
Keywords: Innovation sociale; Living Labs; Recherche partenariale; Transformation sociale

Webinar | Place-based Social Innovation Through Living Labs - Institute Tamarack (2021)
This webinar includes the experiences and insights from two Québec-based organizations with an approach that yields a huge potential for transformative change.
Keywords: Innovation sociale; Laboratoire vivant; Libre accès; Living Labs; Québec; Webinaire

Le living lab, un intermédiaire d’innovation ouverte pour les territoires ruraux ou péri-urbains ? - Fasshauer, Ingrid; Zadra-Veil, Cathy (Innovations, 2020)
L’objectif de cet article est d’analyser une nouvelle forme organisationnelle, le living lab (LL) et sa capacité à favoriser l’innovation territoriale en milieu rural ou péri-urbain. A travers une revue de littérature et la mobilisation de la sociologie de l’acteur-réseau (Callon, 1986 ; Latour, 1987), nous positionnons les living labs comme intermédiaires d’innovation ouverte dont les caractéristiques permettent d’intégrer de nombreux acteurs hétérogènes, établissements publics, entreprises privées, associations et citoyens, sur des projets d’innovation. L’étude d’un LL rural met en évidence la capacité d’une telle structure à reconfigurer des réseaux d’acteurs pour proposer une série de tiers-lieux adaptés aux spécificités des territoires sur lesquels ils s’implantent. Cette recherche permet d’enrichir la réflexion la pérennisation des tiers-lieux ruraux et leurs spécificités par rapport aux espaces urbains.
Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 1 Publisher: De Boeck Supérieur
Keywords: Collaboration; Innovation; Innovation ouverte; Laboratoire vivant; Living Labs; Réservé UdeM; Économie collaborative

Open social innovation dynamics and impact: exploratory study of a fab lab network - Rayna, Thierry; Striukova, Ludmila (R&D Management, 2019)
The aim of this research is to explore the dynamics and impact of open social innovation, within the context of fab labs and makerspaces. Using an exploratory methodology based on 12 semi-structured interviews of fab lab founders belonging to The Centres for Maker Innovation and Technology (CMIT) programme – a network of 170 fab labs located in Eastern Europe – this research explores the impact of an adopting an open approach in relation to the different stages of social innovation (prompts, proposals, prototypes, sustaining, scaling and diffusion, systemic change) as well as social impact. The main results of this study are that while the CMIT programme provided each fab lab with similar initial conditions (identical funding, objectives and rules), the open social innovation approached adopted enabled to give birth to a wide diversity of fab labs, each being very well adapted to the local environment, social needs and constraints and able to deliver social impact in just a matter of years; a result that would be hard to achieve with a centralised top-down approach. The study identified three types of CMITs – Education, Industry and Residential – which could be similar or different depending on the stage of social open innovation. Furthermore, this paper discusses the main difficulties social entrepreneurs encounter as a part of the open social innovation process, as well as means to overcome them. In this respect, this study adds to the literature on fab labs by providing more comprehensive view of the challenges faced by fab labs (and makerspaces) founders, as well as suggestions of strategies enabling to ensure their long-term sustainability.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/radm.12376
Keywords: Innovation ouverte; Laboratoire vivant; Living Labs; Mesure d'impact; Réservé UdeM

University Medialabs: New Learning Spaces for Educational Innovation - Almaraz-Menéndez, Fernando; Martín-García, Teresa; López-Esteban, Carmen (Journal of Strategic Innovation and Sustainability, 2021)
Higher Education Institutions, like many other organizations, are facing pressure from the development of digital technologies as a push towards the digitization of their activities and towards a type of change that some describe as disruptive and that forces them to review their processes and structures. This article describes the case of the medialab of the University of Salamanca, MEDIALAB USAL, as an experience of new learning space in higher education. Its origin is explained from the experiences of citizen technology laboratories and experimental laboratories at the point of intersection between Art, Science and Technology. Its structure and working methods are explained, and its activities are illustrated through the description of four educational innovation projects based on different digital technologies: a mathematics didactics project using AppInventor, Wikipedia as a tool for knowledge generation, Arduino for innovation in the teaching of Fine Arts and a university Hackathon as an activity to introduce students to social and entrepreneurial innovation processes.
Number: 4
Keywords: Collaboration; Durabilité; Europe; Hackathon; Innovation pédagogique; Innovation sociale; Laboratoire vivant; Libre accès; Living Labs; Médialab; Technologies; numérique

Framing improvements of public innovation in a living lab context: Processual learning, restrained space and democratic engagement - Fuglsang, Lars; Hansen, Anne Vorre (Research Policy, 2022)
Public innovation has received increasing attention in recent years. Experiments with new governance structures, such as New Public Management and New Public Governance, have challenged the traditional top-down, internally driven forms of innovation in the public sector and have entailed a search for new forms of open, collaborative and interactive innovation, implying a reframing of public innovation activities. However, introducing these new frames of innovation causes uncertainties in the public sector, necessitating better understanding of how public innovation can be changed to address societal needs. This paper uses materials from case studies of 21 public living labs across Europe to analyse the lessons that can be learned from public sector participation in living labs in terms of their contribution to reframing public innovation. The “frame” construct is used to analyse and provide an understanding of how participation in living labs helps public actors to reframe innovation and address public and societal needs. Three living lab framings for changing public innovation are identified (processual learning, restrained space and democratic engagement), and the degree of intensity of these framings with respect to involving stakeholders and addressing societal challenges is discussed. The paper contributes to knowledge of public sector innovation by extending previous accounts of how public innovation can be improved.
Keywords: Europe; Innovation publique; Laboratoire vivant; Libre accès; Living Labs